MORINDA CITRIFOLIA EXTRACT MOUTHWASH AS ANTIGINGIVITIS: OBAT KUMUR EKSTRAK BUAH MENGKUDU (MORINDA CITRIFOLIA L.) SEBAGAI ANTIGINGIVITIS - Kasuma, Nila; Fajrin, Fildzah Nurul; Aldi, Yufri (TALENTA, 2016)
Gingivitis is a inflamatory mild form of periodontal disease in gingiva. The early stage of gingivitis characterized by the accumulation of plaque, leukocytes, and PMN. Noni (Morinda citrifolia L.) is known to have anti-inflammatory compositions which also affects the activity of leukocytes during inflammation. The research objective was to analyze the clinical effects of mouthwash that contains extracts of noni (Morinda citrifolia L.) on leukocyte levels in the saliva in patients with gingivitis, in order to obtain traditional mouthwash that is economical, readily available, and effective in reducing gingivitis and can be used by the public. Extracts of noni fruit (Morinda citrifolia L.) is given in the form of mouthwashes used for 7 days in a row. Observations conducted on three groups of respondents: group 1 using mouthwash placebo, group 2 using mouthwash noni fruit extract 5%, and group 3 using chlorhexidine 0.1%. The use of mouthwash done in the morning and at night before bed as much as 15 ml for 30 seconds. The results showed a decrease in the number of leukocytes in the group treated with placebo cyst, 5% noni fruit extract, and chlorhexidine 0.1% (p <0.05). Both test preparations equally decreased the number of leukocytes in gingival sulcus in gingivitis patients.